The vigilante poets of Selwyn Academy - Hattemer, Kate (Ember, 2016)
Crackling, witty narration, free roaming between hyperintellectual allusion and shout-outs to Candyland and Mrs. Basil E. Frankweiler, will immediately grip fans of Frank Portman and John Green. The Bulletin, starred review Witty, sarcastic Ethan and his three best friends are students at Selwyn Arts Academy, which has been hijacked by For Art s Sake, a sleazy reality-television show. In the tradition of Ezra Pound, the foursome secretly writes and distributes a long poem to protest the show. They re thrilled to have started a budding rebellion. But the forces behind the show are craftier than they seem. The web of betrayal stretches farther than Ethan could have ever imagined, and it's up to him, his friends, and a heroic gerbil named Baconnaise to save Selwyn.